2011
DOI: 10.21273/horttech.21.5.616
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Gardens as Water-wise Landscapes: A Case Study in Southwestern Europe

Abstract: Spain has undergone a period of uncontrolled urban expansion in a relatively short time-span, affecting people's quality of life in negative ways with significant impacts on the environment and land resources such as water and energy. Many new residential areas have low-density development, based on single-family houses with private gardens. These gardens are usually relatively small in size, but when considered as a whole, they make a substantial contribution to urban green spaces and have an importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
2
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 18 publications
2
18
2
2
Order By: Relevance
“…Although almost 52% of owners were involved in the design of their gardens, professional landscaper intervention was especially important in 25.2% of all cases. This contrasts the results of Fernández-Cañero et al (2011) in Aljarafe, Spain, which showed a higher proportion (86.3%) of owners involved in the design of their gardens.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Although almost 52% of owners were involved in the design of their gardens, professional landscaper intervention was especially important in 25.2% of all cases. This contrasts the results of Fernández-Cañero et al (2011) in Aljarafe, Spain, which showed a higher proportion (86.3%) of owners involved in the design of their gardens.…”
Section: Resultscontrasting
confidence: 99%
“…Garcia et al (2013) identified in the coastal area of Girona (Catalonia, northeastern Spain) four garden typologies (lawn, vegetable, ornamental and tree) and classified them according to their relative water needs and the socioeconomic profiles of the residents who owned them. Studying the Aljarafe region (Andalusia, southern Spain), Fernández-Cañero et al (2011) watered and mainly grown for aesthetic purposes without regard for environmental considerations. Furthermore, the authors reported that decisions to hire a professional maintenance service strongly depend on total garden area.…”
mentioning
confidence: 99%
“…In contrast to agricultural contexts, the look and feel of the landscape is an important consideration for homeowners. Several studies have found that aesthetics are often the primary focus of landscaping decisions, while environmental and other concerns are subsidiary (Fernández-Cañero, Ordovas, & Machuca, 2011;Larsen & Harlan 2006;Spinti & St. Hilaire 2004) .…”
mentioning
confidence: 99%
“…Numerous studies have demonstrated a strong relationship between residential land cover and water use [ Mini et al ., ; Halper et al ., ; Breyer et al , ; Fernández‐Cañero et al ., ]. For example, the amount of irrigated vegetation on residential parcels in Aurora, CO, holds a stronger (and positive) relationship with water use than does vertical structure (e.g., building height) or socioeconomic variables (e.g., income) [ Gage and Cooper , ].…”
Section: Residential Water Usementioning
confidence: 99%